Newly reduced graphene oxide/gold oxide neural-chemical interface on multi-channel neural probes to enhance the electrochemical properties for biosensors. Issue 33 (15th March 2016) - Liu, Ta-Chung; Chu, Chao-Yi; Chen, You-Yin; Chen, San-Yuan
Abstract : The newly neural-chemical interface designed by rGO-wrapped gold oxide nanocomposites on multi-channel neural probes as a biosensor. Abstract : In this study, a facile one-step Cyclic Voltammetry (CV) electrophoresis was proposed for designing a reduced graphene oxide/gold oxide (rGO/AuO x ) modified electrode by using chloride ions (Cl − ) with the simultaneous occurrence of gold oxidation and GO reduction to induce the intimate attachment of negatively charged rGO sheets on the positively charged Au + /Au 3+ clusters by electrostatic interaction. The surface microstructure and the oxygen functional groups of rGO/AuO x can be tuned by controlling the dissolution rate of gold via the deposition scan rate. At a low deposition scan rate, the rGO/AuO x electrode with well-dispersive rGO sheets and large active sites can induce rapid electron transfer to promote H2 O2 detection. The amperometric response results displayed a relative fast response of less than 5 s with a low detection limit of 0.63 μM (S/N = 3). Also, the rGO/AuO x neural-chemical interface can be modified at the multi-channels on neural probe and they exhibited excellent sensing performance to H2 O2 . The results demonstrated that the rGO/AuO x modified electrode integrated with a neural probe using this one-step electrochemical deposition can provide a faster response and higher sensitivity by optimizing and controlling the surface microstructures of rGO/AuO x, which would serve as a platform for medical application such as biosensors for multi-sensing.